Digital and Game-Based Tools in a Course of Spanish for Specific Purposes Diplomacy - Veljković Michos, Maja; Robles Gómez, Margarita (Universidade Aberta, 2024)
The arrival of ICTs in language teaching-learning has been a methodological revolution in this field. However, at present, they have become a necessity due to the global circumstances we live in, and teachers have had to adapt to this new context. On the one hand, a good choice of digital tools when organizing teaching units allows us to introduce, develop, conclude and evaluate our students’ learning. On the other hand, a good choice of digital tools helps us to maintain the motivation of current students and to create community both in face-to-face classes and in virtual classes. These programs allow the development of highly versatile individual and/or collaborative activities. Each one of them allows the development of one or more of the communicative skills: reading and listening comprehension, oral-written and integrated expression. This new panorama also affects the teaching of languages for specific purposes. In addition, students for specific purposes are usually made up of professionals from a certain field of work, with a working day that sometimes does not meet the established schedule, which is why many workers prefer to attend an online language course, in which they study your pace and on your schedule. An example of workers in which their schedule can be easily altered is that of Diplomacy and International Relations. For this reason, this article will present some activities designed using digital tools for a Spanish course on diplomacy and International Relations.
Keywords: e-learning; digital tools; fame-based tools; spanish